Neoadjuvant chemotherapy followed by interval cytoreductive surgery in patients with unresectable, advanced stage epithelial ovarian cancer: a single centre experience - DANE, FAYSAL (SPRINGER HEIDELBERG, 2010)
Background Recent data has shown that the use of neoadjuvant chemotherapy (NAC) significantly reduces tumor burden before optimal cytoreductive surgery (CS) and is associated with an improved overall survival (OS). The aim of our study was to evaluate response to treatment and survival of patients with advanced epithelial ovarian cancer (EOC) who received NAC followed by interval cytoreductive surgery (ICS). Methods Fifty-two patients with advanced EOC treated with NAC followed by ICS were retrospectively analyzed. Response to NAC, progression-free survival (PFS), and OS were evaluated. By using univariate and multivariate analyses, the predicted survival rates by the factors were analyzed. Results Median age of patients at diagnosis were 62 years (range 33-77). The serous cell type was the most common histology (98%). The majority of patients (94%) received a combination therapy of paclitaxel and carboplatin. A median of four cycles of NAC was administered. At the end of NAC, the clinical complete response (CR) with normal clinical examination and normal serum CA 125 level was achieved in 40 patients (77%). Moreover, a radiological CR and a radiological partial response were obtained in 35 patients (67%) and in 16 patients (31%), respectively. ICS was considered standard in 45 (86%) patients. Optimal cytoreduction could be achieved in 43 of 52 patients (83%). After ICS, pathological CR was established in 15 of 52 patients (29%). At the median follow-up of 25 months (range 9-102), 2-year PFS and OS were 31 and 90%, respectively. The median PFS time was 13.3 months (SE 1.1, 95% CI 11-15) and the median OS time was 47.5 months (SE 5.8, 95% CI 36.1-59). The univariate analysis showed that optimal or suboptimal cytoreduction and perioperative blood transfusion were important prognostic factors on OS for patients who received NAC. Patients treated with optimal cytoreduction had significantly better median OS (52.5 months, 95% Cl 45-60) than patients who underwent suboptimal cytoreduction (24.2 months, 95% CI 11.3-37) (P = 0.001). Furthermore, the cytoreduction type (optimal vs. suboptimal), surgical procedure (standard vs. non-standard), and perioperative blood transfusion were independent prognostic factors of OS by multivariate analysis (chi(2) = 9.28, P = 0.002, HR 0.28, 95% CI 0.003-0.37; chi(2) = 4.44, P = 0.035, HR 0.15, 95% CI 0.026-0.87; chi(2) = 9.24, P = 0.002, HR 0.75, 95% CI 0.014-0.79, respectively). Conclusions This study demonstrates that NAC is associated with improved OS for patients with advanced EOC who received NAC followed by ICS. Additionally, our results showed that cytoreduction type, surgical procedure, and perioperative blood transfusion were independent prognostic indicators of OS for patients with advanced EOC who received NAC. Thereafter, NAC may be an alternative treatment to primary cytoreduction.
Keywords: Neoadjuvant chemotherapy; Advanced stage; Epithelial type; Ovarian cancer; PRIMARY DEBULKING SURGERY; SURGICAL CYTOREDUCTION; SURVIVAL; CARCINOMA; EPIDEMIOLOGY; MORBIDITY; PROGNOSIS; IMPACT